The Use of e-Wallet among Gen-Y in Malaysia during the Global Pandemic: Using PLS-SEM Analysis - Yeow Jian Ai; Cheah Chew Sze; Yeo Sook Fern; Tai Hen Toong; Chua Boon Chian (Research Synergy Foundation, 2021)
Traditionally, everyone uses notes and coins or even credit cards and cheques for all business transactions, resulting in several problems such as inconvenience, inefficiency, and ineffectiveness. The limitation of traditional payment may cause delay in payment, high risk of theft, and fraud transaction. To reduce these problems, an e-wallet is introduced, and it helps to reduce fraud as the data stored in the mobile wallet are encrypted. An owner can reduce the limit and receive notification on any transaction. During the global pandemic, consumers are forced to follow the restriction of movement. Stores in Malaysia are closed, and consumers begin to buy things online aggressively. This study aims to determine the factors that affect the use of e-wallet among Gen-Y during the Global Pandemic using PLS-Sem analysis. Snowball sampling was used to gather 181 respondents via online surveys. This study adopted four variables, i.e., perceived ease of use, perceived usefulness, benefits to users, and trust. Of them, two (perceived usefulness and trust) are supported.